2012
DOI: 10.1371/journal.pone.0039299
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Practices by Clinical Service before and after Revised Testing Guidelines in a Swiss University Hospital

Abstract: ObjectivesTo determine 1) HIV testing practices in a 1400-bed university hospital where local HIV prevalence is 0.4% and 2) the effect on testing practices of national HIV testing guidelines, revised in March 2010, recommending Physician-Initiated Counselling and Testing (PICT).MethodsUsing 2 hospital databases, we determined the number of HIV tests performed by selected clinical services, and the number of patients tested as a percentage of the number seen per service (‘testing rate’). To explore the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
(29 reference statements)
0
26
0
Order By: Relevance
“…For the doctors who identified that HIV testing was indicated but stated a low probability that they would perform a test, we did not ask about perceived barriers to testing. We also did not compare reported testing rates with actual rates, although the low figures obtained from the questionnaire agree with our previous study in one of the five centers [6]. Finally, we did not ask about the methods of HIV testing in each centre, specifically, whether any participants use point-of-care rapid testing and whether this influenced the number of tests requested.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For the doctors who identified that HIV testing was indicated but stated a low probability that they would perform a test, we did not ask about perceived barriers to testing. We also did not compare reported testing rates with actual rates, although the low figures obtained from the questionnaire agree with our previous study in one of the five centers [6]. Finally, we did not ask about the methods of HIV testing in each centre, specifically, whether any participants use point-of-care rapid testing and whether this influenced the number of tests requested.…”
Section: Discussionmentioning
confidence: 91%
“…If we assume that all patients attending the EDs we studied are representative of the wider Swiss population, in which HIV seroprevalence is 0.4% [3], then, among the patients presenting to these centers, we would expect 525-700 to be HIV positive (based on Lausanne ED figures, up to 25% of patients present more than once per annum [OH, personal communication]). Using our figures for patient visits per annum (Table S4), we can estimate the HIV testing rate in the EDs we studied (=[tests performed / patients seen] x 100 [6]) by extrapolating the median number of tests performed per doctor per month (=1 test) to the number performed in one year (=1 x 12), and then multiplying by the number of practicing ED doctors. Based on our data in Table S4, the estimated testing rate is 1.1-1.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously described HIV testing rates of B5% in our oncology centre, against a local HIV prevalence of 0.4% [1]. We have since worked with the Service of Oncology to identify, how HIV testing can be optimized, we have conducted a study on investigating barriers in HIV-testing oncology patients (IBITOP) among treating oncologists and their patients.…”
mentioning
confidence: 99%
“…
Background Since the advent of combined antiretroviral therapy (ART), the incidence of non-AIDS-defining cancers (non-ADCs) among HIV-positive patients is rising. We previously described HIV testing rates of <5% in our oncology centre, against a local HIV prevalence of 0.4% [ 1 ]. We have since worked with the Service of Oncology to identify, how HIV testing can be optimized, we have conducted a study on investigating barriers in HIV-testing oncology patients (IBITOP) among treating oncologists and their patients.
…”
mentioning
confidence: 99%